Beyond the User Preferences: Aligning the Prototype Design to the Users' Expectations. Issue 1 (15th December 2014) - Borsci, Simone; Kuljis, Jasna; Barnett, Julie; Pecchia, Leandro
Abstract: It is important for practitioners to conceptualize and tailor a prototype in tune with the users' expectations in the early stages of the design life cycle so the modifications of the product design in advanced phases are kept to a minimum. According to user preference studies, the aesthetic and the usability of a system play an important role in the user appraisal and selection of a product. However, user preferences are just a part of the equation. The fact that a user prefers one product over the other does not mean that he or she would necessarily buy it. To understand the factors affecting the user's assessment of a product before the actual use of the product and the user's intention to purchase the product we conducted a study, reported in this article. Our study, a modification of a well‐known protocol, considers the users' preferences of six simulated smartphones each with different combination of attributes. A sample consisting of 365 participants was involved in our analysis. Our results confirm that the main basis for the users' pre‐use preferences is the aesthetics of the product, whereas our results suggest that the main basis for the user's intention to purchase are the expected usability of the product. Moreover, our analysis reveals that the personal characteristics of the users have different effects on both the users' preferences and their intention to purchase a product. These results suggest that the designers should carefully balance the aesthetics and usability features of a prototype in tune with the users expectations. If the conceptualization of a product is done properly the redesign cycles after the usability testing can be reduced and speed up the process for releasing the product on the market.